R&D in the Belgian Pharmaceutical Sector - Helga De Doncker (National Bank of Belgium, 2006)
The Belgian pharmaceutical sector has been accorded a leading role in the attainment of the R&D investment targets which the EU Member States set themselves as part of the Lisbon strategy. To gain a better insight into that sector's research activities, the NBB conducted an ad hoc survey in 2005, covering pharmaceutical companies active in Belgium in the field of research, production and distribution of drugs for human use. The analysis of the information obtained from that survey makes up the main body of this working paper. The survey results do not only confirm the importance of the research activities conducted by Belgian establishments, but also indicate the frequent cooperation with other research centres and the crucial importance of expertise as a factor influencing the location of such activities in Belgium. The breakdown of the survey results by kind of establishment on the basis of the type of activities conducted in Belgium reveals further clear differences of emphasis in the nature of the R&D activities pursued in Belgium and divergences in the scale of the resources used. The paper also comprises a number of annexes giving additional information on the sector. More particularly, they deal with added value and employment, the indirect effects and profitability of the pharmaceutical companies, and background information on reference reimbursement of drugs.
Keywords: I18; L65; O3; 330; pharmaceutical industry; R&D; reference reimbursement; Forschung; Pharmaindustrie; Belgien